Intrinsic and Extrinsic Motivation in Knowledge Sharing - Gustina, Adin; Indartono, Setyabudi; Darmawati, Arum; Cahyaningrum, Anis Okta (Universitas Negeri Semarang, 2022)
Knowledge sharing is vital in the formation of organizational competitive advantage. This study examine the role of motivation in knowledge sharing. Motivation in this study is divided into two, namely intrinsic motivation and extrinsic motivation. Both mechanisms are explained through Self Determination Theory and Theory Reason Action . Knowledge sharing intention is used to explain the mechanism of motivational influence on knowledge sharing. The results of hypothesis testing indicate that intrinsic motivation has a positive effect on knowledge sharing behavior mediated by knowledge sharing intentions, while extrinsic motivation has no effect on knowledge sharing behavior.